REST-Governed Gene Expression Profiling in a Neuronal Cell Model Reveals Novel Direct and Indirect Processes of Repression and Up-Regulation - Garcia-Manteiga, Jose M.; Bonfiglio, Silvia; Folladori, Lucrezia; Malosio, Maria L.; Lazarevic, Dejan; Stupka, Elia; Cittaro, Davide; Meldolesi, Jacopo (Frontiers in Cellular Neuroscience, 2015)
The role of REST changes in neurons, including the rapid decrease of its level during differentiation and its fluctuations during many mature functions and diseases, is well established. However, identification of many thousand possible REST-target genes, mostly based on indirect criteria, and demonstration of their operative dependence on the repressor have been established for only a relatively small fraction. In the present study, starting from our recently published work, we have expanded the identification of REST-dependent genes, investigated in two clones of the PC12 line, a recognized neuronal cell model, spontaneously expressing different levels of REST: very low as in neurons and much higher as in most non-neural cells. The molecular, structural and functional differences of the two PC12 clones were shown to depend largely on their different REST level and the ensuing variable expression of some dependent genes. Comprehensive RNA-Seq analyses of the 13,700 genes expressed, validated by parallel RT-PCR and western analyses of mRNAs and encoded proteins, identified in the high-REST clone two groups of almost 900 repressed and up-regulated genes. Repression is often due to direct binding of REST to target genes; up-regulation to indirect mechanism(s) mostly mediated by REST repression of repressive transcription factors. Most, but not all, genes governing neurosecretion, excitability, and receptor channel signalling were repressed in the high REST clone. The genes governing expression of non-channel receptors (G protein-coupled and others), although variably affected, were often up-regulated together with the genes of intracellular kinases, small G proteins, cytoskeleton, cell adhesion and extracellular matrix proteins. Expression of REST-dependent genes governing functions other than those mentioned so far were also identified. The results obtained by the parallel investigation of the two PC12 clones revealed the complexity of the REST molecular and functional role, deciphering new aspects of its participation in neuronal functions. The new findings could be relevant for further investigation and interpretation of physiological processes typical of neurons. Moreover, they could be employed as tools in the study of neuronal diseases recently shown to depend on REST for their development.